Biogeochemistry An International Journal - Sebestyen, Stephen D.; Lajtha, Katja; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Biogeochemistry publishes original and synthetic papers dealing with biotic controls on the chemistry of the environment, or with the geochemical control of the structure and function of ecosystems. Cycles are considered, either of individual elements or of specific classes of natural or anthropogenic compounds in ecosystems. Particular emphasis is given to coupled interactions of element cycles. The journal spans from the molecular to global scales to elucidate the mechanisms driving patterns in biogeochemical cycles through space and time. Studies on both natural and artificial ecosystems are published when they contribute to a general understanding of biogeochemistry. .
Keywords: Biogeography; Biotic communities; Environmental chemistry; Life sciences; Biogeosciences; Ecosystems; Environmental Chemistry; Life Sciences